2020
DOI: 10.1002/nau.24519
|View full text |Cite
|
Sign up to set email alerts
|

Alkalinized lidocaine solution as a first‐line local anesthesia protocol for intradetrusor injection of onabotulinum toxin A: Results from a double‐blinded randomized controlled trial

Abstract: Aims: Local anesthesia protocols for intradetrusor onabotulinum toxin A (BoNTA) injection lack standardization. We aimed to determine if an alkalinized lidocaine solution is more effective than lidocaine only. Methods: Patients of both genders aged 18 or above enlisted for intradetrusor BoNTA injection (idiopathic, neurogenic, and bladder pain syndrome) were included in a double-blinded randomized controlled trial after obtaining their informed consent. All participants filled a bladder diary and a urine cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The studies by Pereira e Silva et al, 28 Kocher et al, 24 and Pedraza Sanchez et al 27 evaluated the effectiveness of lidocaine alkalinized with bicarbonate solution.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies by Pereira e Silva et al, 28 Kocher et al, 24 and Pedraza Sanchez et al 27 evaluated the effectiveness of lidocaine alkalinized with bicarbonate solution.…”
Section: Resultsmentioning
confidence: 99%
“…However, there was no standardized measurement for what constituted tolerability. Pain is a subjective experience and influenced by a multitude of factors 28 . Myles et al 36 found 33 mm on a 100 mm VAS to be the upper limit of acceptable pain for postoperative patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations